2002
DOI: 10.1016/s0277-3791(01)00147-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of fluvial sequences in the Mediterranean basin over the last 200ka and their relationship to climate change

Abstract: This paper presents a new correlation of Late and Middle Pleistocene fluvial sedimentary sequences in Greek, Libyan and Spanish river basins and evaluates river response to climate change over the Last Interglacial-Glacial Cycle. Over the past 200,000 years there have been at least 13 major alluviation episodes in the Mediterranean, although the amplitude, frequency and possibly, duration of these events varied significantly across the region. Parts of Oxygen Isotope Stage (OIS) 5 appears to have been periods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
135
4
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(151 citation statements)
references
References 28 publications
9
135
4
3
Order By: Relevance
“…This was well documented for the late Quaternary in the Mediterranean region (e.g. Macklin et al, 2002), during which major alluviation episodes were correlated to cooling trends that lasted generally 10-15 ka and culminated with a massive discharge and deposition of debris. These cooling trends were followed by abrupt warming.…”
Section: The Geomorphic Markersmentioning
confidence: 55%
“…This was well documented for the late Quaternary in the Mediterranean region (e.g. Macklin et al, 2002), during which major alluviation episodes were correlated to cooling trends that lasted generally 10-15 ka and culminated with a massive discharge and deposition of debris. These cooling trends were followed by abrupt warming.…”
Section: The Geomorphic Markersmentioning
confidence: 55%
“…River terraces are known to be preserved in a wide range of settings and basin sizes (Macklin et al, 2002;Bridgland and Westaway, 2008) and have been described here across five catchments in the Wet Tropics region of northeast Australia. This study identified, and classified, dominant terraces across the region, with initial emphasis on available topographic and soils data.…”
Section: Discussionmentioning
confidence: 95%
“…Terraces have formed in all global regions and are commonly studied to understand how rivers have responded to the combined effects of changes in external controls including climate, tectonics, and sea level (Merritts et al, 1994;Macklin et al, 2002;Bridgland and Westaway, 2008) and in internal controls, such as catchment morphology (Coulthard et al, 2005) and reach-specific conditions (Houben, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In both respects this influence might be expected to decline with decreasing latitude, with lessening of the severity of the cold parts of climate cycles. However, there are indications that temperature is a controlling factor in areas well beyond the reach of the Quaternary glaciations; it has, for example, been invoked as significant in the Mediterranean region (Macklin et al, 2002;Martrat et al, 2004). The relation between the interglacial marine terraces of NW Syria and the fluvial terraces of the Kebir has already been noted (above) as evidence that the latter formed during cold stages, which implies that temperature can be the dominant influence as far south as the Mediterranean regions.…”
Section: Differences Between Climatic Zonesmentioning
confidence: 96%
“…With the recognition of nine 100 ky cycles since the 'Mid-Pleistocene Revolution', the potential for matching river terraces to climatic forcing is considerable. Detailed studies of fluvial activity during the last climatic cycle have revealed the importance of climate as a forcing factor (e.g, Macklin et al, 2002;Howard et al, 2004), despite such records being variably compromised by anthropogenic influences. It is therefore clear that cyclic changes in climate would be capable of driving terrace formation, given background uplift.…”
Section: Climatic Forcing Of Terrace Formationmentioning
confidence: 99%